REFOCUS: developing a recovery focus in mental health services in England - Slade, Mike; Bird, V.; Chandler, R.; Clarke, E.; Craig, T.; Larsen, J.; Lawrence, V.; Le Boutillier, C.; Macpherson, R.; McCrone, P.; Pesola, F.; Riley, G.; et al. (Institute of Mental Health, 2017)
Background: Recovery in mental health services is defined as living a satisfying, hopeful, and contributing life even with any limitations caused by illness. An evidence base for understanding and supporting recovery is needed. Objectives: To carry out a programme of linked research studies to understand how mental health services can promote recovery. Design: A two phase, mixed methods study. Phase 1 (theory) involved seven systematic reviews (develop a conceptual framework for recovery; establish its cross-cultural validity; develop a recovery practice framework; review measures of recovery measures; recovery support measures; strengths measures; staff understanding of recovery), development and evaluation of three new measures (INSPIRE for recovery support; IOM for individualised measurement of recovery; SAFE for feasibility assessment), evaluation of existing recovery measure (QPR), national survey, three qualitative studies (conceptual framework validation, staff recoveryoriented practice, black service users), and development of a new manualised REFOCUS intervention. Phase 2 involved a two-site cluster randomised controlled trial of the REFOCUS intervention, with a nested secondary outcome study, process and economic evaluation, interrupted time series analysis, sub-group analysis of black service users, and outcomes comparison. The impact of PPI on the programme was also empirically evaluated. Setting: Six mental health Trusts in England. Participants: 741 community mental health service users, 1,169 mental health staff and 54 expert stakeholders. Interventions: The manualised team-level REFOCUS intervention to increase support for personal recovery. Main outcome measures: Survey: Recovery Self Assessment (RSA). Trial: Questionnaire about the Process of Recovery (QPR), Client Satisfaction Questionnaire (CSQ). Results: Phase 1: the conceptual framework for recovery identified characteristics, stages and processes of recovery. It was cross-culturally valid and applicable to current service users. The recovery practice framework identified four domains of recovery support. INSPIRE, SAFE and IOM were developed and evaluated. The national survey identified differences between team managers (n=22), workers (n=120) and service users (n=108), and found higher recovery orientation was associated with improved recovery. The REFOCUS intervention has two elements: recovery promoting relationships and working practices. Phase 2: the 27-team trial involving 403 service users (297 at follow-up) showed no differences on primary outcomes of QPR (adjusted difference 0.63, 95%CI: -1.4 to 2.3, p=.55), but secondary outcomes of functioning (adjusted difference 5.90, 95%CI 2.6 to 9.2, p<.001) and staff-rated unmet need (adjusted difference -0.80, 95%CI -1·6 to -0·7, p=.03) did improve. Implementation was mixed, and higher-participating teams had higher staff-rated pro-recovery behaviour change (adjusted difference -0·4, 95%CI -0·7 to -0·2, p=·001) and patients had higher QPR Interpersonal scores (adjusted difference -1·6, 95%CI -2·7 to -0·5, p=·005) at follow-up. Intervention-group patients incurred £1,062 (95%CI -£1,103 to £3,017) lower adjusted costs. Black service users did not show improved recovery or satisfaction. Service users who experienced the intervention reported benefits. Conclusions: The REFOCUS intervention has been modified following its evaluation. The REFOCUS Programme provides a theory base for recovery research.